Operations strategy: competition, competencies & trade-offs - Allon, Gad (Henry Stewart Talks, 2013)
Case: Sugar & Spice, Cupcake wars, Competitive benchmarking, Analyzing a competitive threat, Differentiation vs. low cost, Operational efficiency, Comparing operations, Scale, Competitive cost analysis, Fixed costs, Operational advantage, Tradeoff curves
Reviewed at 2020/06/30